Answer:
Hence proved triangle ADE ≅ triangle BCE by Side Angle Side congruent property.
Explanation:
Given:
AD ⊥ AB
CD
BC ⊥ AB
CD
AD = BC
∴ ∠ A = ∠ B = ∠ C = ∠ D =90°
∠ EDC = ∠ ECD
Solution
∠ C = ∠ BCE + ∠ ECD⇒ equation 1
∠ D = ∠ ADE + ∠ EDC⇒ equation 2
∠ C = ∠ D (given)
Substituting equation 1 and 2 in above equation we get
∠ BCE + ∠ ECD = ∠ ADE + ∠ EDC
But ∠ EDC = ∠ ECD (given)
∴ ∠ ADE = ∠ BCE
ED = EC (∵ base angles are same triangle is isosceles triangle)
Now, In Δ ADE and Δ BCE
AD =BC
∠ ADE = ∠ BDE
ED = EC
∴ By Side Angle Side congruent property
Δ ADE ≅ Δ BCE